Activation of Both TLR and NOD Signaling Confers Host Innate Immunity-Mediated Protection Against Microbial Infection - Zhou, Huiting; Coveney, Andrew P.; Wu, Ming; Huang, Jie; Blankson, Siobhan; Zhao, He; O'Leary, D. Peter; Bai, Zhenjiang; Li, Yiping; Redmond, H. Paul; Wang, Jiang Huai; Wang, Jian (Frontiers in Immunology, 2019)
The detection of microbial pathogens relies on the recognition of highly conserved microbial structures by the membrane sensor Toll-like receptors (TLRs) and cytosolic sensor NOD-like receptors (NLRs). Upon detection, these sensors trigger innate immune responses to eradicate the invaded microbial pathogens. However, it is unclear whether TLR and NOD signaling are both critical for innate immunity to initiate inflammatory and antimicrobial responses against microbial infection. Here we report that activation of both TLR and NOD signaling resulted in an augmented inflammatory response and the crosstalk between TLR and NOD led to an amplified downstream NF-kB activation with increased nuclear transactivation of p65 at TNF-a and IL-6 promoters. Furthermore, co-stimulation of macrophages with TLR and NOD agonists maximized antimicrobial activity with accelerated phagosome maturation. Importantly, administration of both TLR and NOD agonists protected mice against polymicrobial sepsis-associated lethality with increased serum levels of inflammatory cytokines and accelerated bacterial clearance from the circulation and visceral organs. These results demonstrate that activation of both TLR and NOD signaling synergizes to induce efficient inflammatory and antimicrobial responses, thus conferring protection against microbial infection.